2017
DOI: 10.1590/1981-22562017020.160145
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with diabetes among the elderly receiving care at a specialized gerontology-geriatric outpatient clinic

Abstract: Objective: To identify the prevalence of diabetes and its relation to associated factors in elderly persons receiving care at a specialist gerontology-geriatric outpatient service. A descriptive cross-sectional study of 301 elderly persons of both genders was performed. Method: The bivariate analysis was performed using the Pearson's Chi-square test for Independence and Fisher's exact test, considering 5% of significance and 95% confidence. A multivariate logistic regression model was adjusted to identify fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 16 publications
3
8
0
6
Order By: Relevance
“…As for age, the elderly have a higher prevalence, which may be justified by the physiological changes inherent in the aging process 24,25 . DM in the elderly is related to a higher risk of premature death, a greater association with other comorbidities and major geriatric syndromes, as well as impairments regarding functional capacity, autonomy and quality of life 26 . It is important to highlight that DM, as well as the metabolic syndrome, which is associated with cardiovascular diseases in adulthood, is increasing in young populations.…”
Section: Discussionmentioning
confidence: 99%
“…As for age, the elderly have a higher prevalence, which may be justified by the physiological changes inherent in the aging process 24,25 . DM in the elderly is related to a higher risk of premature death, a greater association with other comorbidities and major geriatric syndromes, as well as impairments regarding functional capacity, autonomy and quality of life 26 . It is important to highlight that DM, as well as the metabolic syndrome, which is associated with cardiovascular diseases in adulthood, is increasing in young populations.…”
Section: Discussionmentioning
confidence: 99%
“…Large international studies have shown the harms diabetes can cause to older adults, especially in IADL. IADL are more complex and require greater integrity of the most diverse human organ systems for their execution, especially the musculoskeletal and nervous systems (Ramos et al, 2017;Rekeneire & Volpato, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The inner ear has intense metabolic activity, but unlike other organs, it does not have a stored energy reserve, making it more sensitive to fluctuations due to the requirement of resources, specifically glucose and oxygen, necessary for its adequate functioning 6,7 . Thus, hypertension and DM2 are factors that can cause changes in PB 21 .…”
Section: Iibmentioning
confidence: 99%
“…It is estimated that 15.3% of hospital costs of the Unified Health System in Brazil, between 2008 and 2010, were caused by DM. Financial damages are not the only concerns as DM2 can cause damage to the organs and systems of the body, reducing functional capacity and autonomy 1,6 .…”
Section: Introductionmentioning
confidence: 99%